Long live to triangles! Dynamic models for trigonometry - Lasa, Aitzol; Belloso, Nahia; Abaurrea, Jaione (Revista do Instituto GeoGebra Internacional de São Paulo, 2017)
We present a GGB-Book to assist learning and teaching situations for trigonometry. First, we justify the choice to use dynamic geometry software as an instrument to organize mathematical activity, based on a classification of dynamic models based on the “moment of the mathematical activity”. Second, we present a detailed theoretical proposal with guidelines to use it. Finally, we show some results of a practical experience with college students (age 15-16).